2017
DOI: 10.1111/jebm.12277
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and risk of gallstones: A meta-analysis

Abstract: Our study demonstrated a significantly increased risk of gallstones among HCV-infected patients. Further studies are required to clarify how this risk should be addressed in the clinical picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the present study, patients with CHC infection had a higher prevalence of GD than did chronic HBV (CHB)-infected patients. This finding is in agreement with that of previous studies 11 , 12 . Stroffolini et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, patients with CHC infection had a higher prevalence of GD than did chronic HBV (CHB)-infected patients. This finding is in agreement with that of previous studies 11 , 12 . Stroffolini et al .…”
Section: Discussionsupporting
confidence: 94%
“…Wijarnpreecha et al . 12 conducted a meta-analysis to assess the risk of gallstone development in HCV-infected patients; these authors found that such patients had a significantly increased risk of developing gallstones compared to those without an HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there have been observational association of increased gallbladder disease in patient with hepatitis C infection including cholelithiasis thought mainly because of secondary metabolic activity rather than the effect of therapeutic treatment. 10 Similarly, hepatitis B rather than hepatitis C infection has been observed to be associated with gallbladder polyps in targeted population. 11 In our case, despite the patient had previous hepatitis C infection which was adequately treated, the fact that Schistosoma egg was isolated from the polyp, cements being the underlying causative pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Trying to explore associative previous hepatitis C infection, the natural history of the disease is well‐established as being primarily hepatotropic leading to predominantly chronic liver disease including liver cirrhosis. Conversely, there have been observational association of increased gallbladder disease in patient with hepatitis C infection including cholelithiasis thought mainly because of secondary metabolic activity rather than the effect of therapeutic treatment 10 . Similarly, hepatitis B rather than hepatitis C infection has been observed to be associated with gallbladder polyps in targeted population 11 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings were compatible with those of previous studies that revealed negligible or decreased risk of HCC in patients with prior acute cholecystitis. 15,28 Gallstones and HCC share risk factors, such as CHB, 34 CHC, 35 CLD, 36,37 LC, 38 and DM. 39 Therefore, increased cumulative incidence and crude risk of HCC in patients with gallstones are related not by the presence of gallstones but by shared risk factors.…”
Section: Discussionmentioning
confidence: 99%